Retrospective chart review of hospitalizations and costs associated with the treatment of adults with Philadelphia-negative B-cell relapsed or refractory acute lymphoblastic leukemia in Belgium. Issue 6 (2nd November 2017) - Maertens, Johan; Graux, Carlos; Breems, Dimitri; Havelange, Violaine; Wittnebel, Sebastian; Strens, Daniëlle; Hoefkens, Caroline
Abstract : Objectives: To quantify hospitalizations and costs among adults with Philadelphia-negative relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (ALL) who received current salvage chemotherapies in Belgium. Methods: A retrospective chart review identified patients aged ≥18 years and hospitalized between 2005 and 2015 for Ph-negative R/R B-cell ALL. Data were collected from the index date (first diagnosis of R/R ALL) until death or loss to follow-up. The salvage chemotherapy period was defined as the first chemotherapy hospitalization after the index date to the earliest of death, loss to follow-up, last chemotherapy dose plus 30 days, or initiation of hematological stem cell transplantation (HSCT). The primary endpoint was the percent of time in the hospital during the salvage chemotherapy period. Hospitalization costs were reported from the public health care payer perspective. Results: Nineteen patients were included, with median age of 37 years. The average proportion of time patients spent in the hospital during the salvage chemotherapy period was 50.5%. From the index date to death, patients received a mean of 1.8 lines of chemotherapy, most commonly hyper-CVAD (31%). There was a mean of 5.5 inpatient hospitalizations and 40.1 outpatient visits with 40.8 outpatient lab tests. Mean costs per patient were €79, 973 for hospitalization (excluding HSCT), €26, 337 for HSCT, €21, 007 for chemotherapy drugs, and €6, 341 for outpatient management, resulting in a total cost from the payer's perspective of €133, 965 per patient. Conclusion: Adults with Ph-negative R/R ALL spend half the time receiving salvage chemotherapy in the hospital. Their treatment is associated with large reimbursement costs in Belgium.